Neutrophil-to-Lymphocyte Ratio as a Prognostic Biomarker for Patients With Metastatic Renal Cell Carcinoma Treated With Immune Checkpoint Inhibitors: A Systematic Review and Meta-Analysis - Chen, Xiuqiong; Meng, Fanqiao; Jiang, Richeng (Frontiers in Oncology, 2021)
There is increasing evidence to suggest that the neutrophil-to-lymphocyte ratio (NLR) is related to the prognosis of patients with renal cell carcinoma (RCC) treated with immune checkpoint inhibitors (ICIs). However, these findings are inconsistent. The present study was performed with the aim of exploring the utility of NLR in patients with RCC treated with ICIs. For this purpose, a comprehensive search of PubMed, Web of Science, and Embase was performed to find studies evaluating the prognostic value of NLR. The overall survival (OS) and progression-free survival (PFS) were the assessed clinical outcomes. All statistical analysis was performed using Stata version 12.0 software. The combined hazard ratios (HRs) and 95% confidence intervals (CIs) of NLR for OS and PFS were calculated using the random-effect models. Heterogeneity was evaluated based on the I2 value and Cochran’s Q test. Egger’s and Begg’s tests were applied to precisely assess the publication bias. The “trim and fill” method was adopted to perform the sensitivity analysis to determine whether the results were stable. In total, 12 studies encompassing 1,275 patients were included in the final analysis. The results revealed that a high NLR at baseline or pre-therapy was associated with a poor OS (HR, 2.23; 95% CI, 1.84–2.70; p < 0.001) and PFS (HR, 1.78; 95% CI, 1.72–2.09; p < 0.001). During the course of treatment, a decrease in the NLR was associated with a significantly longer OS (HR, 0.34; 95% CI, 0.20–0.56; p < 0.001) and PFS (HR, 0.44; 95% CI, 0.30–0.63; p < 0.001) compared to an increase in NLR. As a preliminary screening of other risk factors, age, sex, race, and IMDC risk may have a certain prognostic value for RCC treated with ICIs. People over 70 years old had better OS compared to people younger than 70 (HR, 0.65; 95% CI, 0.48–0.89). Non-Caucasians treated with immunotherapy had a worse OS (HR, 8.67; 95% CI, 2.87–26.2) and PFS (HR, 2.65; 95% CI, 1.28–5.48) than Caucasians. Males had a worse OS than females (HR, 1.48; 95% CI, 1.14–1.93). Compared with the IMDC favorable risk group, the OS of the IMDC poor risk group was worse (HR, 2.59; 95% CI, 1.56–4.32). There was no significant publication bias or heterogeneity observed in the present study. On the whole, the present study demonstrated that an elevated NLR is associated with an adverse OS and PFS in patients with RCC treated with ICIs. The NLR may thus be used as a readily available prognostic biomarker for these patients. Age, sex, race, and IMDC risk may have potential predictive value for the prognosis of RCC treated with ICIs. However, further investigations are warranted to validate these results.